(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Abnormalities of amniotic fluid volume, including both polyhydramnios and oligohydramnios, may increase maternal and perinatal morbidity and mortality. Among these, oligohydramnios is a significant risk factor that directly affects fetal development and contributes to a higher likelihood of labor complications or the need for cesarean delivery. Oligohydramnios is defined as a reduction in amniotic fluid volume relative to gestational age. Objectives: To determine the prevalence, clinical and paraclinical characteristics, causes of oligohydramnios, and to evaluate pregnancy outcomes in women with oligohydramnios at Dong Nai 2 Hospital in 2025. Materials and Methods: This case-series study included 77 pregnant women with oligohydramnios identified among 650 pregnant women with a gestational age of more than 28 weeks who met the study inclusion criteria. Results: The prevalence of oligohydramnios in this study was 11.85%. The mean maternal age was 29.25 ± 5 years, with women aged 20 to <35 years accounting for 88.31% of cases. Primigravida women represented 62.34% of the study population. Normal gestational weight gain (8–12 kg) was observed in 74.03% of participants. Cephalic presentation was predominant, accounting for 92.21% of cases. The mean fundal height was 28.45 ± 2.6 cm, and the mean abdominal circumference was 92.6 ± 6.0 cm. The average fetal heart rate was 141 ± 5.13 beats per minute. Vertex presentation was observed in 95% of cases. The mean amniotic fluid index was 3.76 ± 1.24 cm. Mean biparietal diameter and femur length were 88.8 ± 5.2 mm and 69.3 ± 3.9 mm, respectively. No cases of fetal congenital anomalies or intra-amniotic infection were recorded. Umbilical cord abnormalities were identified in 2.6% of cases. Isolated oligohydramnios accounted for the majority of cases (94.8%). Cesarean section was the most common mode of delivery among women with oligohydramnios (83.12%). Clear amniotic fluid was observed in 92.21% of deliveries. The mean neonatal birth weight was 3,017 ± 488.69 g, and favorable neonatal outcomes, defined as an Apgar score ≥7, were recorded in 98.7% of newborns. Conclusion: Pregnant women with oligohydramnios generally exhibited clinical and ultrasonographic characteristics within normal ranges. Cesarean delivery was the most common mode of pregnancy termination. Isolated oligohydramnios was identified as the predominant etiology.